Digital Information Systems on Business Agility and Innovation in the Era of Industry 6.0 - Mukhsin Mukhsin; Gusrio Tendra; Suhardjo Suhardjo; Suharti Suharti; Suyono Suyono; Achmad Tavip Junaedi; Andi Andi; Novita Yulia Putri; Yvonne Augustine; Nicholas Renaldo; Sulaiman Musa; Cecilia Cecilia (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The primary objective of this study is to analyze the impact of advanced digital information systems on business agility and innovation within the industry 6.0 framework. Novelty in this research is to develop new dimension of digital information systems, business agility, and innovation. In this quantitative research, data will be collected using a structured questionnaire. The data will then be analyzed using Structural Equation Modeling. The sample size will be a minimum of 210 respondents, in accordance with SEM guidelines. The study confirms that Digital Information Systems (DIS) significantly improve Business Agility and that Business Agility positively influences Innovation. However, Digital Information Systems do not directly improve Innovation. Instead, Business Agility acts as a mediator, meaning that Digital Information Systems enhances Innovation indirectly through Business Agility. This finding highlights the indirect role of Digital Information Systems in fostering Innovation. Simply adopting digital systems is not enough to drive Innovation; rather, organizations must leverage these systems to enhance their agility, which in turn facilitates innovation. Future research should incorporate qualitative approaches (e.g., case studies, expert interviews) to better understand the mechanisms behind agility-driven innovation.